The Practice of Shackles Still Exists: How Is Caregiver Support for Mental Health Recovery for Patients with Mental Disorders? - Sulastri; Sastrawan; Saimi (Science Midwifery, 2022)
The phenomenon of the shackles of people with mental disorders is still common in society. The rights of people with mental disorders are still often ignored. People with mental disorders need the support of a caregiver to live a normal life as usual. This study aims to analyze the factors that cause shackles for people with mental disorders and forms of caregiver support to restore the health of people with mental disorders. The research location is in the Bima district. The type of research used is qualitative with a phenomenological approach. Collecting data using in-depth interviews and participatory observation. Informants in this study are caregivers who treat people with mental disorders. The results showed that the cause of being shackled was because people with mental disorders often roamed around, often resorted to violence, often did the damage, and often carried sharp weapons. The purpose of the shackles is to keep the person with the disorder safe and others around him. Caregiver support in restoring the health of people with mental disorders has not been maximized. Caregiver only feeds and drinks. No medical action is taken to restore the mental health of people with mental disorders. Most of the actions still use the traditional approach, which is taken to a shaman or psychic.